Investigation on formability of three-layer joined Al/Cu/Al sheets annealed at different temperature. Issue 13 (1st September 2020) - Roostaei, Milad; Darabi, Roya
ABSTRACT: Today, the use of multi-layer sheets has expanded widely in various industries. The determination of the forming limit curve for sheets is essential. In this project, three-layer aluminium1100-copper10100-aluminium1100 sheet was produced using an explosive welding method and cold rolling up to 85% strain. Then to eliminate the rolling microstructure and create the isotropic properties and to investigate the effect of annealing temperature on formability, three-layer sheets were annealed at 350°C, 400°C, and 450°C for one hour. Afterward, the numerical and experimental forming limits for these sheets are obtained at room temperature. ABAQUS finite element software and Freudenthal, Cockcroft, and Brozzo ductile fracture criteria were used in numerical method, and punch stretching test was used in the experimental method.